A Modern Technique to Solve the Problem of the Failure of Layers of Multilayer Cylindrical Shells - Emad Toma Karash, Dr.; Abed Alsttar Sediqer, Tymor; Taqi Elias Qasim, Mohammed (International Journal of Engineering and Technology, 2018)
Depending on the theory of the discrete-structure of the thin walls structures, an arithmetical model was proposed for elements of thin, multilayered walls for set layers anisotropic rigid. Assuming that the transverse shear stress is equal to the compression stress at the contact boundary. An elastic slip on the contact surface of adjacent layers is assumed. The problem was solved in a geometrically nonlinear formula with allowance for transverse deformations landslide and compression. The stressed-deformed state of two-layer transversally isotropic cylindrical shells with interphase defects of the structure of the material is studied. The numerical results were compared with the experimental results. The study proved numerically and experimentally data, the change in the kinetic and static conditions of contact on mating surfaces in the solid layers of the various elements of the fine wall structures greatly influences the distribution of compression stress and transverse shear stress deformations. Its ends are rigidly fixed, the work experience of the internal pressure of the uniform intensity of P = 1.11 MPa.Â